Scientific Approach: Model-Based Inquiry in Teaching Narrative - Nurul Azizah Ria Kusrini (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Curriculum 2013 is the latest curriculum created by the government to make the education in Indonesia better. Scientific approach offered in this curriculum is very remarkable to discuss, since almost all educators are talking about this approach. However, most of the educators get trouble and feel confused to apply this approach in teaching English, since it is usually applied in science class. Therefore, this study was written to show the steps of applying this approach in teaching English. This study, used library research, tried to offer new alternative vision to emerge the students’ critical thinking through Model-Based Inquiry, an activity which is able to engage the student to learn more deeply with content and embody of five characteristic of scientific knowledge in which the idea presented in the form of models are testable, revisable, explanatory, conjectural and generative. This study provided the example of teaching narrative text which might be able to be applied in the various final products which could be alternative result of this strategy.